The Islamist turn on ideological grounds: Turkey, Egypt, Pakistan, and Iran in Comparative Perspective - Türegün, Adnan (Middle East Today, 2025)
Chapter 1: Introduction:Islamist Turns, Ideational Perspective, and Comparative Analysis -- Chapter 2: Varieties of Islamism in MENASA Politics -- Chapter 3: The World-Historical Context of Islamisms -- Chapter 4: From Kemalist Modernism to the Turkish–Islamic Synthesis and Turco-Islamism -- Chapter 5: The Egyptian Conundrum: Shades of Modernism and Islamism -- Chapter 6: Transforming the Idea of Pakistan from Nation Building into Defence of Islam -- Chapter 7: Iran: Breaking with Pahlavi Modernism and Shi i Orthodoxy -- Chapter 8: Conclusion: Revisiting Islamism and Comparative Politics.